Possible influence of sex on the relationship between dual-task gait costs and cognitive decline in older adults - Monica Christova; Shane Fresnoza; Christoph Palli; Wolfgang Staubmann; Bernhard Guggenberger (PLoS ONE, 2025)
The impact of cognitive decline in older adults can be evaluated with dual-task gait (DTG) testing in which a cognitive task is performed during walking, leading to increased costs of gait. Previous research demonstrated that higher DTG costs correlate with increasing cognitive deficits and with age. The present study was conducted to explore whether the relationship between the DTG costs and cognitive abilities in older individuals is influenced by sex differences. To address this objective, we conducted a study with 216 elderly participants (age range: 60 to 75 years, 127 females). These underwent Cognitive Functional Dementia (CFD) testing to determine their cognitive abilities and DTG testing to evaluate their gait parameters (gait speed, cadence, stride length, stride variance, and stance phase duration) while performing a backward serial number counting task. We carried out a correlation analysis between the CFD scores and the DTG costs. The DTG costs were calculated as the percentage difference between the gait parameters in single- and in dual-task testing, and the effects were compared considering the factors of sex and age. A significant negative correlation between the CFD scores and the dual-task costs of gait parameters was found only in males. The DTG costs did not differ between the sexes, while women obtained superior scores in the CFD test. The higher DTG costs significantly correlated with older age in men. In summary, our study provides evidence that, unlike in women, the DTG costs during the backward serial number counting task significantly increase in older men, correlating with declines in cognitive performance and increasing age. These findings suggest that the assessment of DT gait characteristics in relation to cognitive decline in older adults may manifest differently between sexes.